Effect of Training and Work Motivation on the Performance of Contract Employees in PT. Telkom Access Treg 3 (Survey on Interference Technicians wifi.id PT. Telkom Access Treg 3) - Wildan Auliya Muttaqin; Rizky Ferrari Oktavian (Journal of Applied Management and Business Administration, 2023)
This study aims to determine the effect of training and work motivation on the performance of contract employees at PT. Telkom Akses Treg 3, specifically for wifi.id interference handling technicians. Training is a business activity to develop one's own abilities both in terms of skills and knowledge to be better in certain competencies. Work motivation is the desire or drive that arises in a person to get maximum work results. Performance is a result or achievement of a person in carrying out his duties during a certain period. This research is a population study in which the wifi.id interference technician PT. Telkom Akses Treg 3 is the respondent in this study, for data collection using a questionnaire with the number of respondents 32 technicians. The analytical method used is quantitative method with descriptive analysis and verification analysis. To process the data, the author uses the help of Microsoft Excel 2013 and SPSS 25 For Windows. This study shows that training and work motivation affect performance either partially or simultaneously.